On the impact of increasing drought on the relationship between soil water content and evapotranspiration of a grassland. Issue 1 (8th May 2020) - Rahmati, Mehdi; Groh, Jannis; Graf, Alexander; Pütz, Thomas; Vanderborght, Jan; Vereecken, Harry
Abstract: Weighable lysimeters were used to study the relation between soil water content (SWC) and the actual evapotranspiration (ETa ) of grassland under two different climate regimes of Rollesbroich and Selhausen but for an identical soil from Rollesbroich. All components of the water balance were determined from 2012 until 2018. Budyko analysis was used to characterize the hydrological status of the studied sites. Wavelet analysis was also applied to study the power spectrum of ETa, vegetation‐height‐adjusted reference evapotranspiration (ETcrop ), and water stress index (WSI) defined as ETa /ETcrop, as well as SWC at three different depths and the coherence between SWC and ETa and WSI. The Budyko analysis showed that 2018 resulted in a shift of both locations towards more water‐limited conditions, although Rollesbroich remained an energy‐limited system. Based on the power spectrum analysis, the annual timescale is the dominant scale for the temporal variability of ETa, ETcrop, and SWC. The results also showed that increasing dryness at the energy‐limited site led to more temporal variability of SWC at all depths at the annual timescale. Wavelet coherence analysis showed a reduction of the phase shift between SWC and ETa at an annual scale caused by the increase in dryness during the measurement period. We found that phase shifts between SWC and ETa and SWC and WSI were stronger at the water‐limited site than at the energy‐limited site. The wavelet coherence analysis also showed that from 2014 to 2018, the control of ETa and WSI on SWC increased due to higher dryness of soil. Core Ideas: Both examined sites shifted toward more water‐limited conditions in dry year 2018. The yearly phase shift between SWC and ETa decreased by greater dryness of 2014–2018. The control of ETa and WSI on SWC increased by greater dryness of 2014–2018.